Dinamika Perjuangan KSPI DALAM Menuntut Hak Kenaikan UMP Tahun 2022 - Amalia, Aanisah Rizq; Kirana, Cantika Sashi; Achwan, Debra Faradiba; Fasikha, Hening Dien; Fitrianingsih, Novita (Journal of Politics and Democracy, 2023)
The economic situation where prices have increased significantly is not only experienced by the Indonesian state but also the world, this is also in line with the increasing needs of the community in terms of clothing and food. Income that does not go hand in hand with rising prices makes it difficult for workers to meet their clothing and food needs. Therefore, a request was made to the government to be able to increase the Provincial Minimum Wage (UMP) so that it could meet the clothing and food needs of the workers. Therefore, this article is written to look at the struggles of the KSPI workers' group in demanding an increase in the UMP in 2022. The method used is a descriptive-qualitative method through in-depth interviews with informants met at research locations and literature studies. From the research we conducted, it is known that KSPI's struggle to demand an increase in the UMP in 2022 by using the strategic concept they have has not produced the desired results and KSPI continues to carry out their struggle by entering Indonesian politics in 2024 by bringing up the issue of increasing the UMP